Kids and Cops: juveniles’ Perceptions of the Police and Police Services - Sanden, Michael (Journal of contemporary criminal justice, 2017)
This study examined the impact of four categories of variables (demographics, neighborhood context variables, contact with the police, and vicarious influence variables) on juveniles’ perceptions of the police and police services. Data analyzed in this study were collected as part of a larger research evaluation that examined the impact of law enforcement efforts in relation to violent crime. Survey responses collected from 423 middle school students were analyzed using a series of OLS regression models. The study found significant results for both dependent variables within all four categories of independent variables. Findings emphasize the importance of including influences from multiple sources into studies that examine juveniles’ perceptions of the police. Policy implications and suggestions for further research are discussed.